Noninvasive, Individualized Cortical Modulation Using Transcranial Rotating Permanent Magnet Stimulator for Voiding Dysfunction in Women with Multiple Sclerosis: A Pilot Trial. Issue 3 (25th March 2022) - Khavari, Rose; Tran, Khue; Helekar, Santosh A.; Shi, Zhaoyue; Karmonik, Christof; Rajab, Hamida; John, Blessy; Jalali, Ali; Boone, Timothy
Abstract : Purpose: Voiding dysfunction (VD) leading to urinary retention is a common neurogenic lower urinary tract symptom in patients with multiple sclerosis (MS). Currently, the only effective management for patients with MS with VD is catheterization. Transcranial Rotating Permanent Magnet Stimulator (TRPMS) is a noninvasive, portable, multifocal neuromodulator that simultaneously modulates multiple cortical regions and the strength of their functional connections. In this pilot trial (ClinicalTrials.gov Identifier: NCT03574610), we investigated the safety and therapeutic effects of TRPMS in modulating brain regions of interest (ROIs) engaged with voiding initiation to improve VD in MS women. Materials and Methods: Ten MS women with VD (having % post-void residual/bladder capacity [%PVR/BC] ≥40% or being in the lower 10th percentile of the Liverpool nomogram) underwent concurrent functional magnetic resonance imaging/urodynamic study (fMRI/UDS) with 3 cycles of bladder filling/emptying, at baseline and post-treatment. Predetermined ROIs and their activations at voiding initiation were identified on patients' baseline fMRI/UDS scans, corresponding to microstimulator placement. Patients received 10 consecutive 40-minute treatment sessions. Brain activation group analysis, noninstrumented uroflow, and validated questionnaires were compared at baseline and post-treatment. Results: No treatment-related adverse effects were reported. Post-treatment, patients showed significantly increased activation in regions known to be involved at voiding initiation in healthy subjects. %PVR/BC significantly decreased. Significant improvement of bladder emptying symptoms were reported by patients via validated questionnaires. Conclusions: Both neuroimaging and clinical data suggested TRPMS effectively and safely modulated brain regions that are involved in the voiding phase of the micturition cycle, leading to clinical improvements in bladder emptying in patients with MS.